Asuhan Kebidanan Komprehensif Pada Ny “ P “ Umur 27 Tahun Di Puskesmas Kairatu Kabupaten Seram Bagian Barat Tahun 2023 - Windatania Mayasari; Santi Aggriani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
The period of pregnancy, childbirth, perurperium, newborns are circumstances that can threaten the life of the mother and the baby even death. One of the goals is to implement comprehensive obstetric care. Comprehensive midwifery care is the care provided by midwives from pregnancy, delivery, newborn, postpartum and until the mother decide to use birth control aimed at providing services an a continuity of care (COC) basis to prevent complications in pregnancy, childbirth, newborns, postpartum and birth control. The method used is descriptive observational research design with case study approach. The results obtained are comprehensive obstetric care provided ranging prom pregnancy, delivery, puerperium, newborn to normal running birth control acceptors.